Virtual reality systems enhance students' achievements in engineering education. Issue 11 (1st November 2016) - Alhalabi, Wadee
ABSTRACT: Virtual reality (VR) is being used for many applications, ranging from medicine to space and from entertainment to training. In this research paper, VR is applied in engineering education, the scope being to compare three major VR systems with the traditional education approach when we do not use any VR system (No-VR). The Corner Cave System (CCS) is compared with the Head Mounted Display (HMD) system. Both of these systems are using a tracking system to reflect the user movements in the virtual environment. The CCS uses only three coordinates: x -, y - and z -axis. The HMD system has six degrees of freedom, the x -, y - and z -axis, as well as the roll, pitch and yaw. Those two systems are also compared with HMD, as a standalone device (HMD-SA) without the tracking system where it has only roll, pitch and yaw. The objective of the study was to evaluate the impact of VR systems on the students' achievements in engineering colleges. The research examined the effect of the four different methods and compared the scores of the students after each test. The experiments were ran over 48 students. Those systems show incredible results.